Peran Gereja dalam Menjaga Kelestarian Ekologi:Menyikapi Kerusakan Hutan Kalimantan oleh Perkebunan Sawit - Nomi Anjelina; Siburian, Hendro Hariyanto; Yuli Berkatni (Sekolah Tinggi Teologi Anugrah Indonesia, 2025)
Kalimantan Island, which is known as one of the lungs of the world, is now experiencing forest destruction due to the expansion of oil palm plantations. Kalimantan's forests, which are rich in biodiversity, are now increasingly threatened by deforestation. The negative impact of deforestation is air and air pollution due to logging and forest fires which threaten humans and wildlife. This research uses qualitative descriptive methods in conducting research. The aim of this research is to offer how the church should play a role in influencing the ecological crisis in Kalimantan, what the church's responsibility is for environmental conservation and what solutions the church can provide to deal with the problem of forest destruction in Kalimantan. The result is that the church has an important role in maintaining ecological sustainability through religious teachings, environmental education, and policy advocacy. The Church builds cooperation with all elements (church congregation, general community, government, NGOs, and community associations) in society to manage and preserve forests, especially in Kalimantan.